2003
DOI: 10.1002/elps.200305542
|View full text |Cite
|
Sign up to set email alerts
|

Improving sensitivity by large‐volume sample stacking using the electroosmotic flow pump to analyze some nonsteroidal anti‐inflammatory drugs by capillary electrophoresis in water samples

Abstract: Large-volume sample stacking using the electroosmotic flow (EOF) pump (LVSEP) has been used to analyze some nonsteroidal anti-inflammatory drugs (NSAIDs) in water samples. With methanol as the run buffer solvent to suppress the EOF, sensitivity was enhanced by 80-100-fold. The sample for the analysis of real water sample was pretreated by solid-phase extraction (SPE). When the method was based on off-line SPE-LVSEP-CE, sensitivity improved by as much as 1000 times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 40 publications
1
61
2
Order By: Relevance
“…Actually, the separation of ten aromatic acids and phenols in methanol was superior to that in water, and sensitivity improvements using LVSEP are more feasible in NACE. The same LVSEP-NACE approach using methanol BGS has been applied to the analysis of nonsteroidal anti-inflammatory drugs (NSAIDs), 48,49 halogenated phenols, [50][51][52] and benzoic acids 52 typically with 50 -300-fold sensitivity increases. Since organic-solvent BGSs with high-pH can be employed to NACE, most weak acids and phenolic compounds, which are easily dissociated at high pH, even in organic solvents, are possible to be concentrated by LVSEP.…”
Section: Lvsep Combined With Nacementioning
confidence: 99%
See 1 more Smart Citation
“…Actually, the separation of ten aromatic acids and phenols in methanol was superior to that in water, and sensitivity improvements using LVSEP are more feasible in NACE. The same LVSEP-NACE approach using methanol BGS has been applied to the analysis of nonsteroidal anti-inflammatory drugs (NSAIDs), 48,49 halogenated phenols, [50][51][52] and benzoic acids 52 typically with 50 -300-fold sensitivity increases. Since organic-solvent BGSs with high-pH can be employed to NACE, most weak acids and phenolic compounds, which are easily dissociated at high pH, even in organic solvents, are possible to be concentrated by LVSEP.…”
Section: Lvsep Combined With Nacementioning
confidence: 99%
“…Macià et al reported that NASAIDs in a real water sample pretreated by SPE was analyzed by LVSEP-NACE, improving the sensitivity by as much as 1000 times. 48,49 Blanco et al developed a determination method for tetrabromobisphenol A and other phenolic compounds in environmental matrices. 50,51 By the off-line coupling of SPE with LVSEP-NACE, the sensitivity was improved by 3300 -4500-fold and 1600 -2200-fold for river water and wastewater Pentachlorophenol and benzoic acids from an acidic aqueous donor solution were extracted to a large pentanol drop hanging at the capillary tip with a Teflon sleeve.…”
Section: Lvsep Combined With Nacementioning
confidence: 99%
“…To make UV detection more sensitive without using any chemical derivatization, various on-column preconcentration techniques [16][17][18][19] have been used such as, fieldamplified stacking [20,21], large-volume sample stacking [22,23], pH-mediated stacking [24][25][26][27], transient isotachophoresis (t-ITP) [28][29][30], transient pseudo-isotachophoresis (tp-ITP) [31,32], and dynamic pH junction [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…When the sample buffer is almost completely out of the column, which is monitored by current, the polarity is switched to the normal configuration, then separation of the analytes can proceed. LVSSPS was used in CE for improving sensitivity in many analytes, such as nonsteroidal anti-inflammatory drugs [13,14], chlorophenols and chlorophenoxy acids [15], naphthalenesulfonates [16], bradykinin and L-enkephalin [17], haloacetic acids [18], trace metals [19,20], etc. These reported papers [13][14][15][16][17][18][19][20] were just demonstrated applications of species in water.…”
Section: Introductionmentioning
confidence: 99%